Comparative study on the concept of buddha nature in degenerating age among dharma practitioners in Sangchen Choekhorling, under Barp gewog, Punakha - Tshering Dema. (CNR, Lobesa : Tshering Dema, 2019)
Includes acknowledgment, Abstract, references (page x-xi) & Appendex(xii-xiii).
Keywords: Buddha nature in degenerating age among dharma practitioners .